A metagenetic approach to determine the diversity and distribution of cyst nematodes at the level of the country, the field and the individual. Issue 23 (December 2015) - Eves‐van den Akker, Sebastian; Lilley, Catherine J.; Reid, Alex; Pickup, Jon; Anderson, Eric; Cock, Peter J.A.; Blaxter, Mark; Urwin, Peter E.; Jones, John T.; Blok, Vivian C.
Abstract: Distinct populations of the potato cyst nematode (PCN) Globodera pallida exist in the UK that differ in their ability to overcome various sources of resistance. An efficient method for distinguishing between populations would enable pathogen‐informed cultivar choice in the field. Science and Advice for Scottish Agriculture (SASA) annually undertake national DNA diagnostic tests to determine the presence of PCN in potato seed and ware land by extracting DNA from soil floats. These DNA samples provide a unique resource for monitoring the distribution of PCN and further interrogation of the diversity within species. We identify a region of mitochondrial DNA descriptive of three main groups of G. pallida present in the UK and adopt a metagenetic approach to the sequencing and analysis of all SASA samples simultaneously. Using this approach, we describe the distribution of G. pallida mitotypes across Scotland with field‐scale resolution. Most fields contain a single mitotype, one‐fifth contain a mix of mitotypes, and less than 3% contain all three mitotypes. Within mixed fields, we were able to quantify the relative abundance of each mitotype across an order of magnitude. Local areas within mixed fields are dominated by certain mitotypes and indicate towards a complex underlying 'pathoscape'. Finally, we assess mitotype distribution at the level of the individual cyst and provide evidence of 'hybrids'. This study provides a method for accurate, quantitative and high‐throughput typing of up to one thousand fields simultaneously, while revealing novel insights into the national genetic variability of an economically important plant parasite.